Lloyd's Register Foundation invested in developing curriculum on food safety in informal markets as part of continuing professional development value chain training for the East African Community (EAC) - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Updated curriculum will support broader East African Community efforts in implementing its Food Safety Strategy. ILRI leads the curriculum update process and provides technical support on implementation.